2013
DOI: 10.1371/journal.pone.0079330
|View full text |Cite|
|
Sign up to set email alerts
|

Moving into Protected Areas? Setting Conservation Priorities for Romanian Reptiles and Amphibians at Risk from Climate Change

Abstract: Rapid climate change represents one of the top threats to biodiversity, causing declines and extinctions of many species. Range shifts are a key response, but in many cases are incompatible with the current extent of protected areas. In this study we used ensemble species distribution models to identify range changes for 21 reptile and 16 amphibian species in Romania for the 2020s and 2050s time horizons under three emission scenarios (A1B = integrated world, rapid economic growth, A2A = divided world, rapid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 61 publications
(84 reference statements)
1
29
0
Order By: Relevance
“…Adverse effects of climate change on protected areas of amphibians have already been elucidated (e.g. D'Amen et al, ; Lemes, Melo, & Loyola, ; Popescu et al, ). For instance, D'Amen et al () evaluated the efficacy of Italian reserve network for amphibians under future climate change scenarios by SDMs.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects of climate change on protected areas of amphibians have already been elucidated (e.g. D'Amen et al, ; Lemes, Melo, & Loyola, ; Popescu et al, ). For instance, D'Amen et al () evaluated the efficacy of Italian reserve network for amphibians under future climate change scenarios by SDMs.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing land surface temperature maps can help identify critical areas of thermal limits for different species and land managers can manage the habitat to increase or decrease temperatures (e.g., manage amount of canopy cover). As with many problems that species face, there will be winners and losers as in Popescu et al (2013) [81], which found that reptiles show mixed responses to climate change across species. Our study suggests that T. c. carolina may benefit from climate change at a landscape scale with increased suitable habitat in the future, assuming that habitat is detectable and accessible, which will be dependent on local scale characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The different biogeographic regions overlapping in Romania will face different types and levels of these changes (Popescu et al in press). Climate change may cause a shift in reptile ranges, although the Carpathian Mountains and the Steppic and Black Sea province of Dobrogea will act as a refuge, being considered critical areas for conservation (Araújo et al 2006, Popescu et al in press).…”
Section: Discussionmentioning
confidence: 99%
“…Climate change may cause a shift in reptile ranges, although the Carpathian Mountains and the Steppic and Black Sea province of Dobrogea will act as a refuge, being considered critical areas for conservation (Araújo et al 2006, Popescu et al in press). To alleviate these threats by conservation activities (e.g., by establishing new protected areas), a key step is predicting the range responses to different climate change scenarios (Franklin 2009, Araújo et al 2011).…”
Section: Discussionmentioning
confidence: 99%